The effects of development induced relocation on livelihoods: The case of people moved from Chiadzwa to Arda Transau. - Dziro, Patience (Midlands State University, 2017)
This study was aimed to analyze the effects of development induced relocation on livelihoods; the case of people moved from Chiadzwa in Marange area to Arda Transau in Odzi. The general objective of the study was to assess the effects of development projects on livelihood of local communities. A sample of forty -four households relocated by Marange Resource mining company representing those who were relocated by the five other mining companies at Chiadzwa was selected using purposive sampling. Data was collected using interview, questionnaires. Results are based on findings from open-ended questionnaires directed at relocated households at Arda Transau and face to face interviews with the representative committee members between mining company and relocated people. Results were that the relocation process brought a lot of challenges on livelihoods as compared to Chiadzwa life. Many people lost their means of living due to relocation and it created a dependency syndrome whereby people are only depending on mining companies as their hope of sustainable livelihood. People from Chiadzwa lost their natural capital, physical capital, as well as social capital. Although mining is one of the lucrative industries in Zimbabwe, the relocated local community is less benefiting from the wealth of their land, only to exacerbate the levels of poverty and loss of livelihoods. The findings show that there is potential on the improvement of livelihoods of relocated people, only lack of will from authorities is lacking, to monitor and evaluate that people are fully compensated. From the study, the results have shown that development projects, particularly in Zimbabwe are trying to maximize their profits at the expense of local communities.